Liana cover in the canopies of rainforest trees is not predicted by local ground‐based measures. (13th April 2019) - Cox, Casey J.; Edwards, Will; Campbell, Mason J.; Laurance, William F.; Laurance, Susan G. W.
Abstract: Lianas (woody climbers) are structural parasites of trees that compete with them for light and below‐ground resources. Most studies of liana–tree interactions are based on ground‐level observations of liana stem density and size, with these assessments generally assumed to reflect the amount of liana canopy cover and overall burden to the tree. We tested this assumption in a 1‐ha plot of lowland rainforest in tropical Australia. We recorded 1072 liana stems (≥1 cm diameter at breast height {dbh}) ha −1 across all trees (≥10 cm dbh) on the plot and selected 58 trees for detailed study. We estimated liana canopy cover on selected trees that hosted 0–15 liana individuals, using a 47‐m‐tall canopy crane. Notably, we found no significant correlations between liana canopy cover and three commonly used ground‐based measurements of liana abundance as follows: liana stem counts per tree, liana above‐ground biomass per tree and liana basal area per tree. We also explored the role of tree size and liana infestation and found that larger trees (≥20 cm dbh) were more likely to support lianas and to host more liana stems than smaller trees (≤20 cm dbh). This pattern of liana stem density, however, did not correlate with greater liana coverage in the canopy. Tree family was also found to have a significant effect on likelihood of hosting lianas, with trees in some families 3–4 times more likely to host a liana than other families. We suggest that local ground‐based measures of liana–tree infestation may not accurately reflect liana canopy cover for individual trees because they were frequently observed spreading through neighbouring trees at our site. We believe that future liana research will benefit from new technologies such as high‐quality aerial photography taken from drones when the aim is to detect the relative burden of lianas on individual trees. Abstract : Abstract : Las lianas (bejucos leñosos), son parásitos estructurales de árboles que compiten con ellos por luz y recursos del subsuelo. La mayoría de los estudios sobre interacciones entre lianas y árboles se basan en observaciones realizadas desde el suelo sobre la densidad de tallos de lianas y su tamaño. Generalmente, se asume que estas observaciones reflejan la cantidad de lianas que cubren el dosel y la carga que representan para los árboles. Nosotros probamos esta suposición en una parcela de 1 hectárea en un bosque de tierras bajas en Australia tropical. Registramos 1072 tallos de lianas (≥1cm diámetro a la altura del pecho {dap}) en árboles de más de 10cm de dap en la hectárea, y seleccionamos 58 árboles para un estudio más detallado. Estimamos la cobertura del dosel por lianas en los árboles seleccionados usando una grúa de 47 metros de alto. Los árboles seleccionados tenían entre 0 y 15 lianas. No encontramos correlaciones significativas entre la cobertura del dosel por parte de las lianas y tres medidas que son usadas comúnmente para medir la abundancia de lianas desde el suelo: número de tallos de lianas por árbol, biomasa de lianas por árbol, y área basal de lianas por árbol. También exploramos el papel del tamaño de los árboles y la infestación de lianas y encontramos que los árboles más grandes (≥ 20cm dap) eran más propensos a tener lianas y a tener más tallos de lianas que árboles más pequeños (≤ 20 cm dap). Sin embargo, este patrón de densidad de tallos de lianas no se correlacionó con una mayor cobertura de lianas en el dosel. La familia taxonómica a la que pertenecen los árboles también tuvo un efecto significativo en la probabilidad de que los árboles tuvieran lianas, con ciertas familias teniendo una probabilidad de 3 a 4 veces más alta de tener lianas que otras familias. Sugerimos que las medidas tomadas desde el suelo sobre la infestación local de lianas en los árboles tal vez no reflejan la cobertura de las lianas en el dosel por árbol, dado que frecuentemente en nuestro sitio de estudio, las lianas se extienden a árboles vecinos. Creemos que estudios futuros se pueden beneficiar de nuevas tecnologías como las fotografías aéreas de alta resolución tomadas desde drones, cuando el objetivo sea detectar la carga relativa de las lianas en árboles individuales.